Pengenalan dan Penerapan Fortifikasi Gizi Seimbang Serta Personal Hygiene di SDN Ampelan 2 Bondowoso - Adhitya Wardhono; Ciplis Gema Qori’ah; Agung Nugroho Puspito; Mohammad Ubaidillah; Daniyah Basalamah; Farokhatun Nazilah; Atiqa Zahra Aulia; Adelia Niandhita Palupi; M. Alif Muzhaffar; Dini Nurin Alfiyah; Muchammad Savero Sulthan Marzi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Education is a basic right needed to improve the quality of human resources (HR). Education also influences the process of increasing each individual's insight and knowledge. In various contexts, problems with education often arise due to a lack of awareness regarding the importance of education. Likewise at SDN Ampelan 2, the lack of education regarding education and individual awareness of the importance of nutrition and health is one of the obstacles. In this social project, the main objective which is the main basis is how schools can provide education regarding healthy lifestyles, personal health and academics. By introducing intensive, active and persuasive learning, this social project takes an approach by showing educational videos as an interactive media approach. Providing PHBS material, Fill My Plate, washing hands, brushing teeth and English related to health sciences, as well as intensive supporting academic learning is a social project effort to increase the strengthening of balanced nutrition and awareness of the importance of personal health. SDN Ampelan 2's enthusiasm for this social project is supporting evidence for the changes that have occurred regarding healthy lifestyles, personal health and education. The post-test results showed that the students at SDN Ampelan 2 were able to achieve an understanding of the material with an average score above 80%. Other changes also occur in behavioral aspects of health, knowledge, cleanliness and discipline. Changes in the application of ethics also support positive changes for students at SDN Ampelan 2.